Recent Advances in Single-Particle Tracking: Experiment and Analysis - Szwabiński, Janusz; Weron, Aleksander (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Entropy, titled "Recent Advances in Single-Particle Tracking: Experiment and Analysis", contains a collection of 13 papers concerning different aspects of single-particle tracking, a popular experimental technique that has deeply penetrated molecular biology and statistical and chemical physics. Presenting original research, yet written in an accessible style, this collection will be useful for both newcomers to the field and more experienced researchers looking for some reference. Several papers are written by authorities in the field, and the topics cover aspects of experimental setups, analytical methods of tracking data analysis, a machine learning approach to data and, finally, some more general issues related to diffusion.